Volume 6A: Pipeline and Riser Technology 2014
DOI: 10.1115/omae2014-23690
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hydrostatic Collapse of Pipes Using Finite Element Analysis

Abstract: A pipeline’s resistance to collapse is governed by geometric imperfections, material properties and residual stresses. The offshore pipeline design code DNV-OS-F101 provides a method for predicting collapse of pipelines with diameter to wall thickness (D/t) ratios between 15 and 45. This paper examined the various factors that could influence the collapse resistance of several pipe geometries, such as ovality, eccentricity, material stress-strain behavior and residual stresses in the hoop and longitudinal dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…However, Abdideh and Khah (2018) presents casing collapse phenomena as abnormal displacements of rock formations on the casing leading to collapse. Bastola et al (2014) examined the factors influencing pipe's collapse resistance and concluded that effects are small for 3D models with length to diameter (d/t) ratios above 10, and that an increase in initial ovality would lead to a decrease in the pipe's resistance to collapse. Salehi et al (2009) showed that reservoir compaction results in 4 different casing collapse mechanism; buckling, bending, traction and shear.…”
Section: Collapse/burst Failurementioning
confidence: 99%
“…However, Abdideh and Khah (2018) presents casing collapse phenomena as abnormal displacements of rock formations on the casing leading to collapse. Bastola et al (2014) examined the factors influencing pipe's collapse resistance and concluded that effects are small for 3D models with length to diameter (d/t) ratios above 10, and that an increase in initial ovality would lead to a decrease in the pipe's resistance to collapse. Salehi et al (2009) showed that reservoir compaction results in 4 different casing collapse mechanism; buckling, bending, traction and shear.…”
Section: Collapse/burst Failurementioning
confidence: 99%
“…Collapse analysis was continued following the sizing analysis. For analysis, both ends of a section of pipe were fixed in all directions, and because the length of the pipe was 10 times longer than its diameter, the influence of the boundary conditions could be ignored in the center cross-section along the longitudinal direction of the pipe [5]. External pressure was applied uniformly to the outer surface of the pipe.…”
Section: Collapse Analysis Conditionsmentioning
confidence: 99%
“…They also confirmed that the collapse performance could be improved by promoting the out-of-roundness phenomenon in cross-sections. Bastola et al [5] conducted finite element analysis and confirmed that residual stress could reduce the resistance to collapse pressure by as much as 20%, and that the residual stress along the circumferential direction of the pipe were more significant on collapse performance than those along the longitudinal direction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations